Odorant Receptors and Odorant-Binding Proteins as Insect Pest Control Targets: A Comparative Analysis - Venthur, Herbert; Zhou, Jing-Jiang (Frontiers in Physiology, 2018)
Recently, two alternative targets in insect periphery nerve system have been explored for environmentally-friendly approaches in insect pest management, namely odorant-binding proteins (OBPs) and odorant receptors (ORs). Located in insect antennae, OBPs are thought to be involved in the transport of odorants to ORs for the specific signal transduction of behaviorally active odorants. There is rich information on OBP binding affinity and molecular docking to bioactive compounds as well as ample 3D crystal structures due to feasible production of recombinant proteins. Although these provide excellent opportunities for them to be considered as pest control targets and a tool to design pest control agents, the debates on their binding specificity represent an obstacle. On the other hand, ORs have recently been functionally characterized with increasing evidence for their specificity, sensitivity and functional roles in pest behaviors. However, a major barrier to use ORs for semiochemical discovery is the lack of 3D crystal structures. Thus, OBPs and ORs have not been analyzed comparatively together so far for their feasibility as pest control targets. Here, we summarize the state of OBPs and ORs research in terms of its application in insect pest management. We discuss the suitability of both proteins as pest control targets and their selection toward the discovery of new potent semiochemicals. We argue that both proteins represent promising targets for pest control and can be used to identify new super-ligands likely present in nature and with reduced risk of resistance development than insect pesticides currently used in agriculture. We discuss that with the massive identification of OBPs through RNA-seq and improved binding affinity measurements, these proteins could be reconsidered as suitable targets for semiochemical discovery.